gwp 2020
DOI: 10.24149/gwp382
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary and Mandatory Social Distancing: Evidence on COVID-19 Exposure Rates from Chinese Provinces and Selected Countries

Abstract: We thank Johns Hopkins University for assistance with the data. We would also like to acknowledge helpful comments by Ron Smith. The views expressed in this paper are those of the authors and do not necessarily reflect those of the Federal Reserve Bank of Dallas or the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 18 publications
6
40
1
Order By: Relevance
“…In contrast, the greatest potential for reducing transmission is observed for horizontal distancing 23 . This simulation is in line with international experience, indicating greater effectiveness of horizontal isolation over vertical isolation for flattening the epidemic curve 24,25,26,27,28 .…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, the greatest potential for reducing transmission is observed for horizontal distancing 23 . This simulation is in line with international experience, indicating greater effectiveness of horizontal isolation over vertical isolation for flattening the epidemic curve 24,25,26,27,28 .…”
Section: Discussionsupporting
confidence: 87%
“…One study finds that the lockdown of Wuhan, China (the city in which the virus was first identified) reduced inflow into, out of and with Wuhan (Fang, Wang, and Yang 2020), thus reducing infections outside of Wuhan. Another study using Chinese data finds that mandatory, but not voluntary, social distancing is effective at flattening the pandemic curve (Chudik, Pesaran, and Rebucci 2020).…”
Section: Analyses Of Covid-19 and Associated Policiesmentioning
confidence: 99%
“…Chudik, Pesaran and Rebucci (2020) [8] contrast government-mandated social distancing policies with voluntary self-isolation in an SEIR model. They decompose the population, N , into two categories: the exposed N E and the rest, N I , which are isolated.…”
Section: Introductionmentioning
confidence: 99%
“…We provide a forecast of the total number of cases: the total number of cases so far plus s>today M (s). Alternatively, we use the formula for the total number of cases from the model m, which is approximately given by (7), (8), and 95. Selection of K. Our choice of K is often limited by data availability.…”
mentioning
confidence: 99%